Republican scientific-practical conference of nursing specialists "Peculiarities of nursing care services in oncology" - Center of Excellence of Healthcare and Pharmacy Specialists informs, (Slauga. Mokslas ir praktika, 2020)
Respublikinė mokslinė praktinė slaugos specialistų konferencija ,,Sveikatos priežiūros paslaugų ypatumai onkologijoje“.